Biostratigraphy, Thermal Maturity and Paleoenvironment of the Basal Part of Gombe Formation from Gongola Sub-Basin, Northern Benue Trough, North Eastern Nigeria - Idris, Mustapha Dahiru; Yandoka, Babangida M. Sarki; Ayuba, M. K.; Abdullahi, Ibrahim M. (Journal of Science Research and Reviews, 2025)
The basal part of the Gombe Formation in the Gongola sub-basin (Northern Benue Trough) was investigated using integrated lithostratigraphic, palynological and foraminiferal analyses of (13) outcrop samples (GM-1 to GM-13) to establish age and paleoenvironment. The succession is characterized by recurrent coarsening-upward cycles, basal claystone/mudstone grading into interbedded siltstones and fine sandstones and locally capped by medium–coarse sandstones with bioturbated greenish–brown shales (Thalassinoides), localized ironstone development and ferrogenised sands. Palynological assemblages from most samples yield Maastrichtian marker taxa (e.g., Tricolporopollenites sp., Cingulatisporites ornatus, Zlivisporites blanensis, Proteacidites dehaani, Distaverrusporites simplex), while the microfossil record is dominated by arenaceous benthic foraminifera (e.g., Haplophragmoides spp., Miliammina inflata, Trochammina spp., Ammobaculites coprolithiformis, Reophax guineana). Integration of these data indicates a Late Campanian–Maastrichtian age with strong emphasis on the Maastrichtian and a depositional setting interpreted as marginal-marine to shallow inner-neritic influenced by deltaic–estuarine progradation. The abundance of terrestrially derived palynomorphs, freshwater indicators (e.g., Botryococcus) and charred plant fragments, together with the absence of calcareous/planktic foraminifera, point to strong terrestrial input, intermittent freshwater influence and dysoxic bottom conditions. Some samples (GM-2, GM-9, GM-12) show low fossil recovery.